The 12C* Hoyle state in the inelastic 12C + 12C reaction and in 24Mg* decay. (23rd February 2016) - Morelli, L; Bruno, M; D'Agostino, M; Baiocco, G; Gulminelli, F; Abbondanno, U; Barlini, S; Bini, M; Casini, G; Cinausero, M; Degerlier, M; Fabris, D; et al.
Abstract: The reaction 12 C + 12 C at 95 MeV has been studied at the Legnaro Laboratories of INFN with the GARFIELD + RCo apparatus. Data have been analyzed in order to investigate the decay of the Hoyle state of 12 C*. Two different data selections have been made. The first one corresponds to peripheral binary collisions where the quasi-projectile is excited to the Hoyle state and the target has been left in the ground state. The second selection allows for studying central events with the formation of a 24 Mg* and the Hoyle state is obtained as a step of the decay chain. The characteristics of the Hoyle state decay are very similar in the two samples and point to a mainly sequential decay through the population of an intermediate 8 Begs, with a small contribution (∼1.1%) from simultaneous three α -particle processes.